Guidelines for the use of flow cytometry and cell sorting in immunological studies (third edition). Issue 12 (7th December 2021) - Cossarizza, Andrea; Chang, Hyun‐Dong; Radbruch, Andreas; Abrignani, Sergio; Addo, Richard; Akdis, Mübeccel; Andrä, Immanuel; Andreata, Francesco; Annunziato, Francesco; Arranz, Eduardo; Bacher, Petra; Bari, Sudipto; et al.
Abstract: The third edition of Flow Cytometry Guidelines provides the key aspects to consider when performing flow cytometry experiments and includes comprehensive sections describing phenotypes and functional assays of all major human and murine immune cell subsets. Notably, the Guidelines contain helpful tables highlighting phenotypes and key differences between human and murine cells. Another useful feature of this edition is the flow cytometry analysis of clinical samples with examples of flow cytometry applications in the context of autoimmune diseases, cancers as well as acute and chronic infectious diseases. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid. All sections are written and peer‐reviewed by leading flow cytometry experts and immunologists, making this edition an essential and state‐of‐the‐art handbook for basic and clinical researchers.